کتابات طلبة المرحلة الجامعیة الأولى فى حمامات جامعة أسیوط کمصدر من مصادر المعلومات :دراسة میدانیة - د. منصور سعید محمد (المجلة الدولية لعلوم المكتبات والمعلومات)
The present study is a field study that aimed at identifying the extent towhich the components of information sources are available in university students'writings in Assiut University bathrooms. The study consisted of an introduction, apractical section and a conclusion. One of the most remarkable findings of thestudy is that the components of information sources are available in universitystudents' writings in Assiut University bathrooms, albeit with differentcharacteristics and percentages. Its cover is comprised of the bathrooms of sixfaculties, its body is comprised of 579 writings, and its pages, totaling 148 pages,are the walls and doors of 37 bathrooms. The walls have 111 pages (66.8%) vis-à-vis 37 pages (33.2%) for the doors.These writings are distributed to six chapters according to the bathroomsof the faculties under study. The biggest chapter is the chapter on the writings ofthe bathrooms of the Faculty of Social Work with a percentage of 31.4%, and thesmallest chapter is the one on the writings of the bathrooms of the Faculty ofScience with a percentage of 5.4%. As for the languages in which these writingsare written, Arabic comes first with a percentage of 49.7%, followed by Englishwith a percentage of 39.9%, and then Arabic and English together with apercentage of 9.8%. They take the form of statements (35.4%), symbols (16.9%),words (7.1%), drawings (2.9%), and figures and numbers (2.6%).